ВПЛИВ ФОРМИ СТРУМУ ІНДУКТОРІВ ТА МАГНІТНОГО ПОТОКУ ЕЛЕКТРОМАГНІТУ НА ЕЛЕКТРОМАГНІТНУ СИЛУ, ЩО ДІЄ НА РОЗПЛАВЛЕНИЙ МЕТАЛ В АКТИВНІЙ ЗОНІ МАГНІТОДИНАМІЧНОГО НАСОСУ - А.А. Щерба; М.О. Ломко (Праці Інституту електродинаміки Національної академії наук України, 2023)
The processes of creating an electromagnetic force acting on the molten metal in the active zone of a magnetodynamic pump are studied depending on the spectral composition of the higher harmonic components of the current in the channel and the induction of the magnetic flux induced by an electromagnet. The peculiarities of the regulation of the magnitude and direction of the resultant vector of this force, the favorable conditions of the vibrational action on the molten metal in the active zone are defined. Ref. 8, fig. 4, tables 3.